Pengembangan e-modul interaktif berbasis aplikasi book creator mata pelajaran produk kreatif dan kewirausahaan kelas XII BDP SMK PGRI 13 Surabaya - Juliana, Ira; Sulistyowati, Raya (Jurnal Pendidikan Ekonomi (JUPE), 2023)
The development of an interactive e-module based on the book creator application in the subject of Creative Products and Entrepreneurship aims to complement learning and as an alternative used in teaching and learning. This type of research used the ADDIE development model. The average validation score for material experts is 90% with very feasible criteria, the average validation result for media experts is 96% with very feasible criteria, the average validation result for linguists is 96% with very feasible criteria. The response value of the field trial students obtained an average of 87.1% with very decent criteria.